Incorporating hydrodynamics into spatiotemporal metabolic models of bubble column gas fermentation. Issue 1 (27th October 2018) - Li, Xiangan; Griffin, Derek; Li, Xueliang; Henson, Michael A.
Abstract: Gas fermentation has emerged as a technologically and economically attractive option for producing renewable fuels and chemicals from carbon monoxide (CO) rich waste streams. LanzaTech has developed a proprietary strain of the gas fermentating acetogen Clostridium autoethanogenum as a microbial platform for synthesizing ethanol, 2, 3‐butanediol, and other chemicals. Bubble column reactor technology is being developed for the large‐scale production, motivating the investigation of multiphase reactor hydrodynamics. In this study, we combined hydrodynamics with a genome‐scale reconstruction of C. autoethanogenum metabolism and multiphase convection–dispersion equations to compare the performance of bubble column reactors with and without liquid recycle. For both reactor configurations, hydrodynamics was predicted to diminish bubble column performance with respect to CO conversion, biomass production, and ethanol production when compared with bubble column models in which the gas phase was modeled as ideal plug flow plus axial dispersion. Liquid recycle was predicted to be advantageous by increasing CO conversion, biomass production, and ethanol and 2, 3‐butanediol production compared with the non‐recycle reactor configuration. Parametric studies performed for the liquid recycle configuration with two‐phase hydrodynamics showed that increased CO feed flow rates (more gas supply), smaller CO gas bubbles (more gas–liquid mass transfer), and shorter column heights (more gas per volume of liquid per time) favored ethanol production over acetate production. Our computational results demonstrate the power of combining cellular metabolic models and two‐phase hydrodynamics for simulating and optimizing gas fermentation reactors. Abstract : Gas fermentation has emerged as a technologically and economically attractive option for producing renewable fuels and chemicals from carbon monoxide (CO) rich waste streams. LanzaTech has developed a proprietary strain of the gas fermentating acetogen Clostridium autoethanogenum as a microbial platform for synthesizing ethanol, 2, 3‐butanediol, and other chemicals.